Rice chromosome SNP density for five rice varieties. - Hiroki Ikeda (510280) (2025)
Dots indicate SNP density in a 100-kb window size for Udai21 (a), Koshihikari (b), Nipponbare (c), Kasalath (d), and IR 58 (e). Colors indicate the 12 chromosomes of the rice genome.